Ražošanas procesa uzlabošana akvakultūrā - Davidjuka, Irina (Latvijas Universitāte, 2014)
Maģistra darba „Ražošanas procesa uzlabošana akvakultūrā” mērķis ir nodrošināt Latvijas zivsaimniecības nozares akvakultūras sektora pilnvērtīgu attīstību. Pēc nozares problēmu analīzes tika izvēlēta viena problēma - akvakultūras sektora zema ražošanas efektivitāte. Problēmas novēršanai maģistra darbā autore izstrādā projektu, kura ietvaros akvakultūras uzņēmumiem tiek iegādātas un uzstādītas ūdens recirkulācijas sistēmas, kas spēs palielināt zivju krājumus ūdenstilpnēs ar kopējo platību 100 ha. Darbs sastāv no: 82 lappusēm, 15 attēliem, 23 tabulām un 39 pielikumiem. Atslēgas vārdi: projekts, projektu vadīšana, zivsaimniecība, akvakultūra, zivju sugas.

The objective of master's “Improvement of the Production Process in Aquaculture” the aim is to develop Latvian fisheries aquaculture sector. Master includes analysis of existing problems in the fisheries sector and provides the solutions. Aquaculture which is one of the fishery sector activities have been taken as the base. After the analysis of the problems was chosen one of it – the aquaculture sector has low effectiveness of the production process. For the problem solution author of master propose to organize the project. In the frame of the project will be purchased and established water recirculation system for the aquaculture companies. The water recirculation systems will be able to increase fish stocks in the water basin with a total area of 100 ha. Master paper consists of 82 pages, 15 pictures, 23 tables and 39 annexes. Key words: project, project management, fishery, aquaculture, fish species.
Improvement of the Production Process in Aquaculture
Keywords: Vadībzinātne